CHRONIC EFFECTS OF DETERGENT SURFACTANT (LINEAR ALKYLBENZENE SULFONATE I LAS) ON THE GROWTH AND SURVIVAL RATE OF SEA BASS (Lates calcalifor Bloch) LARVAE - Sri Rejeki; Desrina .; Andi Rahmat (JOURNAL OF COASTAL DEVELOPMENT, 2005)
Sea bass (Lates calcal&r Bloch), one of the economically important marine fish, is getting more important for marine-culture. This fish is categorized as a euryhaline species, i.e. with a wide salinity tolerance, range 32 — 35 ppt, and in the river, estuarine and mangrove areas with the salinity between 0 - 25 ppt. The adult of sea bass is spawn in marine waters while the larvae and juvenile are is spawn mostlv found in the estuarine. Estuarine water is known as a good nursery and feeding ground, however it is also knownias a pollutant trap. Therefore, the larvae of seabass and other euryhaline species are very susceptible to this condition.Suryizctant detergent Linear A lkyl—benzene SuU"onate (LAS} is a non—ionic so]? detergent, with a long straight carbon chain, has a powerful cleaning capability; it is toxic to aquatic organisms, and however it is biodegradable. Therefore, it is widelv used for cosmetic and household purposes. This research was done to find out the chronic effect (LCM-96 hours) and acute ejects of detergent LAS on the larvae of sea bass (Lates calcaliver Bloch}. A Bioassay method was applied to jind out the acute toxicity, and Probit Analyses is used to find out the LC 50-96 hours of detergent LAS on sea bass larvae. Randomized design was carried out to observe the chronic ejects on the growth and survival rate ofthe sea bass larvae. There were six treatments applied, i. e, : A (0% of LC ,,,-96 hours); B (5% of LCM-96 hours}; C (10% of LCM-96 hours); D (/5% of LC50-96 hours); E (20% of LCM-96 hours); F (25% ofLCm-96 hours).The results showed that the treatment of LCM-96 hours of detergent LAS on sea bass larvae, I. I8 mg/I, was considered as moderatelv high toxicity. The absolute biomass growth of sea bass larvae was not afected by sub·lethal concentrations of detergent ALS, however, chronic concentrations of detergent LAS tyfected the daily growth rate of sea bass larvae signyicantb¤ (o<0.0l). As a conclusion, the acute toxicity of LAS detergent on sea bass (Lates calcaliver Bloch} larvae was l. I 8 mg/l. The sub—lethal concentrations of detergent LAS on the sea bass larvae did not influence the biomass growth and survival rate but affected the daib¤ growth rate of sea bass larvae significantly. The sea bass larvae exposed to the sub lethal concentrations of LAS detergent hr 30 days resulted in the gill damage, i.e..· hypertrophy, hyperplasia, telengeastases and melanization of the gill. The congestion and vacuolar degeneration ofthe liver were also observed.